Welfare implications on management strategies for rearing dairy calves: A systematic review. Part 1–feeding management - Carulla, Patricia; Villagrá, Arantxa; Estellés, Fernando; Blanco-Penedo, Isabel (Frontiers in Veterinary Science, 2023)
Calves are very susceptible to stress in the early stages of life, and it is necessary to ensure maximum welfare. Feeding management has been identified as a major risk factor for calf health and welfare at this stage. However, the management protocol for calf rearing and its impact on animal welfare is unclear. A systematic review of different management strategies for rearing dairy calves according to the three spheres of animal welfare was conducted using an electronic search strategy. In this review, management strategies were studied to identify scientific gaps, to know the welfare problems of these animals in order to prioritize actions and future research and to study the interpretive approach of this management from the three welfare spheres. A protocol was used to analyze and extract information from the studies. Of the 1,783 publications screened, only 351 met the inclusion criteria for the management or welfare of calves’ items. The publications identified in the search can be divided into two main groups feeding and socialization, based on the main topic of the publication. The main topics that emerged from the search in the feeding management group were milk replacer, colostrum, and weaning, divided into the three main areas of biological functioning and health, natural life and affective states or cognitive judgement. The main issues to be addressed were the different types of feed consumed by animals from birth to weaning and the weaning management. It has been found that the most researched issues are colostrum and solid starter feed management. Unresolved issues were highlighted, such as the lack of a clear protocol for the administration of milk replacers to reduce hunger and the best management of weaning to reduce stress.